PENERAPAN MEDIA TIGA DIMENSI TERHADAP HASIL BELAJAR MATEMATIKA ANAK TUNAGRAHITA RINGAN - Masruroh, Siti (Jurnal Pendidikan Khusus, 2017)
Abstract : Child tunagrahita class 1 in SLB C Pertiwi Ponorogo not yet able to know the concept of numbers well. When taught to recognize the numbers 1 to 10 children still have difficulty in spelled out correctly. Children need to be taught again so that children can recognize the concept of numbers by how to count, sort, write the number 1 to 10 appropriate teaching materials. The purpose of this study is to improve the ability of learning outcomes mathematics child tunagrahita mild by applying three-dimensional media. This research uses quantitative approach and pre-experiment type research, using One Group research design, Pretest, Post test design. The results showed a significant increase, seen from the ability of children memalaui aspects of counting, sorting, writing the numbers 1 to 10. This is evidenced by the analysis of data that shows the value of Z arithmet = 2.20 greater than the value of Z table = 1.96 which means The application of three-dimensional media can improve the learning outcomes of mathematics.     Keywords: Three Dimensional Media Applications, Mathematics Learning Outcomes